FunFun: ITS‐based functional annotator of fungal communities - Danil V. Krivonos; Dmitry N. Konanov; Elena N. Ilina (Ecology and Evolution, 2023)
Abstract The study of individual fungi and their communities is of great interest to modern biology because they might be both producers of useful compounds, such as antibiotics and organic acids, and pathogens of various diseases. And certain features associated with the functional capabilities of fungi are determined by differences in gene content. Information about gene content is most often taken from the results of functional annotation of the whole genome. However, in practice, whole genome sequencing of fungi is rarely performed. At the same time, usually sequence amplicons of the ITS region to identify fungal taxonomy. But in the case of amplicon sequencing there is no way to perform a functional annotation. Here, we present FunFun, the instrument that allows to evaluate the gene content of an individual fungus or mycobiome from ITS sequencing data. FunFun algorithm based on a modified K‐nearest neighbors algorithm. As input, the program can use ITS1, ITS2, or a full‐size ITS cluster (ITS1‐5.8S‐ITS2). FunFun was realized as a pip‐installed command line instrument and validated using a shuffle‐split approach. The developed instrument can be very useful in the fungal community comparing and estimating functional capabilities of fungi under study. Also, the program can predict with high accuracy the most variable functions.